Collective Online Learning Practice in Higher Education in Biak, Indonesia: Navigating Digital Disparity - Dewi Zulaiha; Pegiawan Basopi (Journal of Islamic Studies and Education, 2026)
Digital disparity significantly challenges online learning implementation in remote area in Indonesia, particularly in Papuan context. This study explores the unique online learning model adopted by English Education (PBI) students in private university in Biak, Papua as a resilient response to infrastructure limitations. Using a qualitative case study approach, data were gathered through semi-structured interviews and field observations. The study involved 25 students, along with key stakeholders and lecturers, to provide a comprehensive perspective on the local educational ecosystem. The results reveal that students navigate digital gaps through "collective online learning" practices, characterized by resource sharing, group-based digital access, and a hybrid synchronization of offline-online interactions. This model transcends simple technical usage, reflecting a socio-cultural adaptation to geographical and connectivity constraints. These findings suggest that in areas with high digital disparity, a collective approach is essential for educational sustainability. The study offers practical insights for policymakers to design hybrid frameworks that are culturally and technically situated for the Papuan context.